URUN REMBUG PENYELESAIAN KONFLIK MELALUI FOCUS GROUP DISCUSSION DENGAN BRIGADE MOBILE POLRI - Ali, Syarif; Kusmana, Agus (Batara Wisnu : Indonesian Journal of Community Services, 2024)
Conflict in various dimensions is part of the dynamics of national and state life, but resolving conflicts peacefully, fairly and with legal certainty and respecting Human Rights (HAM) is a target that we want to achieve together. The Indonesian Police Mobile Brigade Corps, as the bearer of responsibility for domestic security, seeks to find the best solution to resolve conflicts in various regions in Indonesia, including utilizing the results of research, thought and analysis from academics. Therefore, the activity of inviting academics to the forum is one of the strategies of the Indonesian Police Mobile Brigade Corps to obtain data and information that has so far not been disseminated by academics. On the other hand, for academics, the exchange of ideas and thoughts is an event for Community Service (PKM) with the main partner of the Indonesian Police Mobile Brigade Corps. The method used in this PKM activity is Focus Group Discussion (FGD) which is attended by PN Veteran Jakarta academy, comes from the Faculty of Economics and Business, Faculty of Social and Political Sciences, Faculty of Law, Faculty of Public Health and the Indonesian Police Mobile Brigade Corps. The results of the PKM provide advice to the POLRI Mobile Brigade Corps to collaborate with the press, present a friendly and pro-community POLRI figure, and form a buzzer to educate the public and socialize the policies of the POLRI Mobile Brigade Corps in an effort to increase awareness and awareness of the negative impacts of conflict